A qualitative study of teachers’ perception on the need for reviewing the senior secondary school economics curriculum in Kosofe Local Government, Lagos State (2020)
Nigeria is faced everyday with economic crisis and challenges, despites the teaching and learning of economics as a subject in secondary schools and tertiary institutions. There was a need to investigate the state of the curriculum used, especially at the secondary level. Thus, this paper examined the perception on the need for reviewing the senior secondary school economics curriculum. The study was guided by two research questions. The phenomenology qualitative research approach was adopted. Five public secondary schools in Kosofe Local Government Area, Lagos State were selected using the simple random sampling technique. Ten Economics teachers were purposively selected from the schools for the study. Interview sessions were conducted using 'Interview Guide on the Perception of Teachers about the Economics Curriculum (IGPTEC)'. Thematic approach was used to analyse the data collected. Findings revealed that, current Economics curriculum content has not been updated since year 2008, teachers 'privy to the curriculum opined that there is a need for the integration of recent economic issues such as SDGs 2030, SMEs drive, enlighten about agriculture's impact on Nigerian economy. Hence, it was recommended that Economics curriculum needs to accommodate recent economic realities in order to achieve positive changes peculiar to economic concepts